Cardiac Blood Pool Imaging — A Clinical Comparison between Red Blood Cells Labeled with 99mTc in vivo and in vitro and 99mTc-Labeled Human Serum Albumin - Dahlström, J. A.; Carlsson, S.; Lilja, B.; Mattsson, S.; Pettersson, C. (Nuklearmedizin - NuclearMedicine, 1979)
In 25 patients undergoing radiocardiographic determination of ventricular function, three methods for blood pool imaging were compared. 99mTc was used to label human serum albumin (HSA) and red blood cells (RBC) in vivo or in vitro. The activity concentration of 99mTc in blood was measured during 2 hrs after injection and a significantly higher concentration was found with RBC compared to HSA already after 15 min. The left ventricular to background count rate ratio was significantly lower for HSA after 90 min compared to RBC. There was no statistical difference in 99mTc activity concentration in blood or in left ventricular to background count rate ratio during the two hrs when the two RBC-labeling procedures were compared. 99mTc-labeled RBC are superior to 99mTc-labeled HSA for gated blood pool studies and especially for repeated determinations of ventricular function. Because the in vivo labeling is the most convenient method it has been adopted as the clinical routine at our hospital.